Somatic embryogenesis on plumule and radicle explants obtained from warm water hydroprimed wheat (Triticum aestivum L.) cv. Kunduru and cv. Cakmak Seeds - Kahriz, Parisa Pourali; Kahriz, Mahsa Pourali (Penerbit Universiti Kebangsaan Malaysia, 2017)
Advances in wheat biotechnology and in vitro somatic embryogenesis (SE) provide new openings to faster application of these techniques in functional genomic studies, genetic engineering and plant breeding. This study reports in vitro SE using plumule and radicle explants of two wheat cultivars Cakmak and Kunduru on MS induction medium amended with varying concentrations of 2,4-D. Both plumule and radicle explants were regenerative and induced variable number of somatic embryos per explant. Explants and treatment methods affected in vitro SE irrespective of the genotypes used in the study. Although 100% SE was noted on both explants of two cultivars, plumule explants of both genotypes induced heavy and larger friable calli followed by somatic embryogenic calli in terms of weight. Plumule explants also induced large numbers of shoot buds and somatic embryo-induced maturing shoots per explant. The in vitro raised plantlets were successfully rooted followed by hardening and acclimatisation in pots containing peat moss in mist house. After 7 days from weaning, these plants were transferred to a shade house to grow and set flowers. Water spray containing 0.50 μg of NPK (1:1:1) was given at intervals of 4 d to enhance success rate of acclimatised plants. Success rates of 96 and 80% were noted on plumule and radicle-induced plants, respectively. It is further concluded that use of this novel methodology would favorably facilitate its use in genetic transformation and functional genomic studies.